Activities of Pedagogical Libraries as Sources of Pedagogical Information - Navickaitė, Gražina (Knygotyra, 1985)
Universal compulsory education is a significant achievement of Soviet cultural life. It has caused increased requirements for school teachers in the sphere of pedagogics and teaching efficiency. Specialized pedagogical libraries as centres of pedagogical information are of great help for school teachers. Based on branch-residential principles they can be characterized as three-aspect units. First, their activities include coordination and support of the branch information services by a central library with a more comprehensive collection of materials, by a technical services unit that coordinates selection acquisition, processing and delivery of materials. Second, they coordinate the cooperation of branch libraries and provide extension services. Third, they support and stimulate contacts with the scientific pedagogical information system.